A Nacre‐Inspired Separator Coating for Impact‐Tolerant Lithium Batteries. Issue 51 (6th November 2019) - Song, Yong‐Hui; Wu, Kai‐Jin; Zhang, Tian‐Wen; Lu, Lei‐Lei; Guan, Yong; Zhou, Fei; Wang, Xiu‐Xia; Yin, Yi‐Chen; Tan, Yi‐Hong; Li, Feng; Tian, Te; Ni, Yong; et al.
Abstract: The commercial ceramic nanoparticle coated microporous polyolefin separators used in lithium batteries are still vulnerable under external impact, which may cause short circuits and consequently severe safety threats, because the protective ceramic nanoparticle coating layers on the separators are intrinsically brittle. Here, a nacre‐inspired coating on the separator to improve the impact tolerance of lithium batteries is reported. Instead of a random structured ceramic nanoparticle layer, ion‐conductive porous multilayers consisting of highly oriented aragonite platelets are coated on the separator. The nacre‐inspired coating can sustain external impact by turning the violent localized stress into lower and more uniform stress due to the platelet sliding. A lithium‐metal pouch cell using the aragonite platelet coated separator exhibits good cycling stability under external shock, which is in sharp contrast to the fast short circuit of a lithium‐metal pouch cell using a commercial ceramic nanoparticle coated separator. Abstract : A nacre‐inspired coating is fabricated to improve the impact tolerance of the separator in a lithium battery via efficient energy dissipation. Remarkably, the pouch cell using the nacre‐inspired porous aragonite platelet coated separator performs with much lower instantaneous open‐circuit voltage change and faster voltage recovery than the cell using the commercial ceramic nanoparticle coated separator under external impaction.